2009
DOI: 10.1590/s0102-695x2009000400022
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of infusions (tea) of Solidago microglossa DC. (Asteraceae) on the cell cycle of Allium cepa

Abstract: DC. (Asteraceae) no ciclo celular de Allium cepa". A espécie medicinal Solidago micrglossa DC., a qual é nativa da América do Sul, é usada como infusão (chá) para desordens estomacais na medicina popular. O objetivo desse estudo foi avaliar o potencial efeito citotóxico dessas infusões no ciclo celular de Allium cepa. Folhas in natura de três populações dessa espécie foram utilizadas no preparo das infusões em duas concentrações: 1,75 mg/mL e 14 mg/mL. Células de raízes de cebola (Allium cepa) foram usadas com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
(24 reference statements)
3
10
0
2
Order By: Relevance
“…The concentrations (20g/L) (mitotic index=11) and (12.5g/L) (mitotic index=12) also inhibited mitosis with respect to the control by 26% and 20% respectively. This decrease in the mitotic index as the concentration of the extracts increases coincides with the results of other medicinal extracts, for example extracts of Psidium guajava, 7 of Solidago microglossa 14 and of Pterocaulon polystachyum. 15…”
Section: Discussionsupporting
confidence: 82%
“…The concentrations (20g/L) (mitotic index=11) and (12.5g/L) (mitotic index=12) also inhibited mitosis with respect to the control by 26% and 20% respectively. This decrease in the mitotic index as the concentration of the extracts increases coincides with the results of other medicinal extracts, for example extracts of Psidium guajava, 7 of Solidago microglossa 14 and of Pterocaulon polystachyum. 15…”
Section: Discussionsupporting
confidence: 82%
“…The evaluation of the effect caused by infusions carried out with Solidago microglossa DC. leaves on the Allium cepa cell cycle, Bagatini et al (2009) observed that the highest concentration tested (14 mg/ml) caused a reduction in the mitotic index, thus demonstrating the antiproliferative effect of this species.…”
Section: Resultsmentioning
confidence: 70%
“…The same was observed in Artemisia verlotorum Lamotte by Souza et al (2010). Bagatini et al (2009), while studying Solidago microglossa D.C., found antiproliferative activity in the extract with the highest concentration compared to the negative control.…”
Section: Allium Cepa Testmentioning
confidence: 95%
“…The same was observed in Artemisia verlotorum Lamotte by Souza et al (2010). Bagatini et al (2009), while studying Solidago microglossa D.C., found antiproliferative activity in the extract with the highest concentration compared to the negative control.The A. cepa test can be considered a bioindicator for monitoring the genotoxic potential of several chemical compounds. Chauan et al (1999) used meristematic cells of A. cepa to study the clastogenic potential of the pesticides cypermethrim and fenvalerate and obtained a good correlation with the test in mammals.…”
mentioning
confidence: 95%